TREASURE HUNT : CODING WITH CODY. 3 - Grellen; Tan, Liqing Vivien (Singapore : WS Education, 2023)
Lily and Logan are excited to introduce Grandma to Cody. Grandma has been having some difficulties with her knee and needs some help moving around. Can Cody help Grandma find her lost things?This is the third book in the Coding with Cody series, which introduces fundamental coding concepts to kids. It discusses if-then conditions that can lead a computer or machine to carry out different actions based on varying scenarios
Includes activity sheet
Keywords: Coding theory -- Juvenile literature; Computer programming -- Juvenile literature